2019
DOI: 10.1002/pits.22298
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive assessment course: Two decades later

Abstract: We wish to thank all of the faculty who completed this survey and who work tirelessly to provide students with evidence-based training in cognitive assessment. We thank Randy Floyd who reviewed an early draft of this manuscript and Vincent Alfonso for providing the original survey.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 39 publications
(64 reference statements)
5
49
0
Order By: Relevance
“…At a minimum, training should focus on the importance of accurate, standardized administration, common errors (see Lockwood et al, 2019), and on interpretation. Third, as a significant number of special educators and educational diagnosticians administer NRTs, future research should examine the training that these professionals receive in areas crucial for proper test administration, such as psychometrics, statistics, and standardized procedures (Lockwood & Farmer, 2019); relatedly, future research into the NRT administration fidelity of these practitioners would also appear crucial. Finally, only a third of participants indicated that their district uses CBM data to aid in special education identification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At a minimum, training should focus on the importance of accurate, standardized administration, common errors (see Lockwood et al, 2019), and on interpretation. Third, as a significant number of special educators and educational diagnosticians administer NRTs, future research should examine the training that these professionals receive in areas crucial for proper test administration, such as psychometrics, statistics, and standardized procedures (Lockwood & Farmer, 2019); relatedly, future research into the NRT administration fidelity of these practitioners would also appear crucial. Finally, only a third of participants indicated that their district uses CBM data to aid in special education identification.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was created to gather information regarding participant demographics as well as data regarding district-level (a) NRT and (b) CBM practices. Survey items were generated based on recent peer-reviewed articles (e.g., Lockwood & Farmer, 2019) and textbooks (e.g., Breaux & Lichtenberger, 2016; Waugh & Gronlund, 2013). The survey was reviewed by nine content experts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 In keeping with the most widely accepted view of cognition, the Cattel-Horn-Carrol theory, 10 it is important to consider a comprehensive analysis of cognitive abilities in intelligence testing, including specific auditory processing skills. [11][12][13] Recent research reveals evidence of need for ongoing development of cognitive assessment to more accurately incorporate more aspects of the CHC model. 14,15 We argue that development of such tests should consider a lifespan approach, the ability to screen briefly, and a simplified scoring and reporting system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, test authors provide dedicated worksheets as part of their record forms for the calculation of differences between specific cognitive ability composites and between subtests. Likely due to a constellation of these factors, as much as 65% and 33% of instructors teach students to interpret comparisons between composite scores and between subtests, respectively (Lockwood & Farmer, 2019). It is then no surprise that practitioners report interpreting score comparisons in practice (Benson et al, 2019;Kranzler et al, 2020;Sotelo-Dynega & Dixon, 2014).…”
mentioning
confidence: 99%